(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This study examines the urgent need for enhancing the organizational and economic mechanisms of Uzbekistan’s textile industry to improve its export potential and competitiveness in global markets. The analysis focuses on benchmarking the industry against global leaders such as China, Turkey, and Bangladesh, identifying best practices that can be adapted to the Uzbek context. The research provides recommendations for adopting digital transformation, optimizing production processes, and implementing innovative export strategies to drive growth. The findings underscore the importance of strategic investments in digital tools, workforce development, and global market integration to ensure sustainable competitiveness.